N-Cadherin modified lipid bilayers promote neural network formation and circuitry. Issue 44 (31st October 2017) - Zobel, K.; Choi, S. E.; Minakova, R.; Gocyla, M.; Offenhäusser, A.
Abstract : Biomimetic supported lipid bilayers serve as a new compatible platform for investigating the function of synaptic adhesion proteins in neural network formation, synaptic connectivity and maturation. Abstract : Neural adhesion, maturation, and the correct wiring of the brain to establish each neuron's intended connectivity are controlled by complex interactions of bioactive molecules such as ligands, growth factors, or enzymes. The correct pairing of adjacent neurons is thought to be highly regulated by ligand-mediated cell–cell adhesion proteins, which are known to induce signaling activities. We developed a new platform consisting of supported lipid bilayers incorporated with Fc-chimera synaptic proteins like ephrinA5 or N-cadherin. We extensively characterized their function employing a quartz crystal microbalance with dissipation (QCM-D), calcium imaging, and immunofluorescence analysis. Our biomimetic platform has been shown to promote neural cell adhesion and to improve neural maturation at day in vitro 7 (DIV7) as indicated by an elevated expression of synaptophysin.